Hak Asasi Manusia dan Islam - Moh. Solehuddin (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2018)
Muslims become the best people that ever existed on earth, because the freedom to express their opinions is absolutely guaranteed. Islam obliges nahi munkar (forbidding evil) against any behavior that endangers Islam and man. The mandate to bring goodness and dakwah is the responsibility of every Muslim. If Muslims abandon the obligation of amar ma'ruf nahi munkar, then they no longer have the privilege of being the best people. Allah says (that means), “You are the best people born to mankind, telling the ma'ruf, and preventing from being evil, and having faith in God If Our Expert believe, surely it is better for they, among them are believers, and most of them are the wicked ones.”